Preferensi Petani terhadap Benih Kentang Industri pada Mitra Perusahaan PT Indo Agro Resources - Haoro, Putri Yaohanida; Sitepu, Rasidin Karo Karo (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Potatoes are a food crop that has a high economic value that can provide benefits for farmers, traders, and processed food industry entrepreneurs. The demand for potato consumption increases every year, this is an opportunity for farmers to increase their productivity. This study aims to identify the attributes of industrial seed potatoes at PT Indo Agro Resources and analyse farmers' preferences. The analysis method uses descriptive statistics and conjoin analysis. Using primary data collected through interviews for 70 respondents. The results showed that the combination of attributes that fulfil farmers' preferences are seed potatoes that are free from plant disrupting organisms, plant morphology with a short harvest age, tuber size that is in accordance with the standard, have an affordable seed purchase price, and get assistance in the production process. To increase farmers' production, the company should provide seeds with new seed varieties that are free of plant disrupting organisms.